Acute type a aortic intramural hematoma complicated with preoperative hemopericardium: early and late surgical outcome analyses - Chun-Yu Lin; Ming-Chang Kao; Hsin-Fu Lee; Meng-Yu Wu; Chi-Nan Tseng (Journal of Cardiothoracic Surgery, 2024)
Abstract Background Acute type A aortic intramural hematoma (ATAIMH) is a variant of acute type A aortic dissection (ATAAD), exhibiting an increased risk of hemopericardium and cardiac tamponade. It can be life-threatening without emergency treatment. However, comprehensive studies of the clinical features and surgical outcomes of preoperative hemopericardium in patients with ATAIMH remain scarce. This retrospective study aims to investigate the clinical features and early and late outcomes of patients who underwent aortic repair surgery for ATAIMH complicated with preoperative hemopericardium. Methods We investigated 132 consecutive patients who underwent emergency ATAIMH repair at this institution between February 2007 and August 2020. These patients were dichotomized into the hemopericardium (n = 58; 43.9%) and non-hemopericardium groups (n = 74; 56.1%). We compared the clinical demographics, surgical information, postoperative complications, 5-year cumulative survival rates, and freedom from reoperation rates. Furthermore, multivariable logistic regression analysis was utilized to identify independent risk factors for patients who underwent re-exploration for bleeding. Results In the hemopericardium group, 36.2% of patients presented with cardiac tamponade before surgery. Moreover, the hemopericardium group showed higher rates of preoperative shock and endotracheal intubation and was associated with an elevated incidence of intractable perioperative bleeding, necessitating delayed sternal closure for hemostasis. The hemopericardium group exhibited higher blood transfusion volumes and rates of re-exploration for bleeding following surgery. However, the 5-year survival (59.5% vs. 75.0%; P = 0.077) and freedom from reoperation rates (93.3% vs. 85.5%; P = 0.416) were comparable between both groups. Multivariable analysis revealed that hemopericardium, cardiopulmonary bypass time, and delayed sternal closure were the risk factors for bleeding re-exploration. Conclusions The presence of hemopericardium in patients with ATAIMH is associated with an elevated incidence of cardiac tamponade and unstable preoperative hemodynamics, which could lead to perioperative bleeding tendencies and high complication rates. However, patients of ATAIMH complicated with hemopericardium undergoing aggressive surgical intervention exhibited long-term surgical outcomes comparable to those without hemopericardium.